In defense of embargoed improperly property - Rioja Bermúdez, Alexander (2011)
This article develops the existing scholar doctrine and case law on third party claims to ownership as an institution that guarantees the ownership rights of the person affected by the precautionary measure of attachment in proceedings in which he is not a party, thereby analyzing the grounds and conditions required to enforce said institution.